From ancient Rome to colonial Mexico : religious globalization in the context of empire - Wright, David, 1956-; Marco Simón, Francisco (University Press of Colorado, 2023)
"From Ancient Rome to Colonial Mexico compares the Christianization of the Roman Empire with the evangelization of Mesoamerica. With the analysis of empire and globalization and a postcolonial perspective on religion, the book proposes the method of "analytical comparison" to conceptualize affinities and differences between geographies"--